Encyclopaedic dictionary of Phoenician culture. - Ercolani, Andrea, 1969-; Xella, Paolo (Peeters, 2018)
"The Encyclopaedic Dictionary of Phoenician Culture (EDPC) is the result of a wide-ranging international project and is intended to be an in-depth and up-to-date standard reference work for Phoenician studies. It is a series in the form of an encyclopaedia with the structure of a dictionary, comprising about 2,000 entries, written by circa 200 contributors from 20 different countries. Current knowledge on the Phoenicians and Carthaginians (with close attention to their various interactions with other cultures) will be presented as a sequence of themed volumes, all closely interrelated, dealing respectively with religion, language and written sources, socio-economic life, and archaeological sites of both the Levant and the Central and Western Mediterranean. As part of a collection, each volume should be considered as belonging to a set: in one sense independent but at the same time inseparable from the others in respect of both the amount of information and the network of cross-references linking the various lemmata. The present volume, dedicated to historical characters, is a compendium of historical and historically documented individuals, arranged alphabetically and organized using criteria that are meant to be as consistent as possible. Like the thematic volumes to follow, the present volume is a reference work: it is based on a piece by piece reconstruction of the whole of 'Phoenician' history (understood in its widest sense) through its various protagonists at every level."--Publisher website